INOVASI PUBLIK PERSPEKTIF TRIPLE HELIX: STUDI DI KABUPATEN SUMBAWA NUSA TENGGARA BARAT - Muhammad Firmansyah; Agus Suman (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
Development innovation is now an instrument that continues to be driven by the central government towards local governments in Indonesia. With innovation, the limitations of development can work even with a limited budget. This study describes the development and innovation constraints of triple helix based in Sumbawa Regency, West Nusa Tenggara Province. Data related to all innovations was obtained from the interview process with the Sumbawa Regency Bappeda and several other sources. From each innovation will be selected that contains the triple helix element from each of these innovations. O'Samawa is an innovation model in the form of a community formed based on an MoU between the Sumbawa Bappeda, UTS (Sumbawa Technology University) and business people. The goal of O'Samawa is to facilitate businesses to increase product and packaging capacity, facilitate access to capital and market networks. Activities that have been carried out in O`Samawa are training, product exhibitions, seminars, building a joint store (shop) and building an online market website.